Integra????o do design thinking com m??todos ??geis em projetos de desenvolvimento de software - G??es, Roberto de Souza (2017)
Design Thinking and agile methods, when used in an innovative and dynamic environment, aiming the creating products and solutions to support business and to increase satisfaction, bringing solutions to the current problems and that also generate future business for the company. This study was carried out with the objective of verifying how the companies that adopted the Design Thinking and the agile methods did to integrate it, from the creation of the solution of the initiatives to be development-using software. Design Thinking is able to aid in the generation of new ideas centered on the human, through research and prototyping techniques, in a fast and multidisciplinary way. Agile methods are widely used and studied as a method of software development. This study was carried out through a multiple case study with data collection for a qualitative research, in companies or in technology departments, where this technology is used as the main tool to manage and generate business. On this research was found three different types of integration between the models, sequentially. The first with a queue between the final solution definition stage and the beginning of software development, the second, without a queue between the final solution definition stage and the beginning of software development, the third model is the use of Design Thinking and agile methods together and simultaneously, as a single process. These different integration models aim to meet the projects needs regarding to complexity and size, as well as the uncertainties in which companies are subject throughout project life cycle.